Demand for energy in Western India - National Council of Applied Economic Research (New Delhi, 1965)
This Volume is the third of the regional studies of demand and supply of energy in the Council's Programme of work covering the four regions, the Southern, eastern, western and northern. The reports on the southern and eastern regions were published in 1962 and 1963. The present study of the western region covers the States of Maharashtra, Gujarat, Madhya Pradesh and the Union territories of Goa, Daman and Diu.
Keywords: "Energy developmentEconomic aspects India, Western"